2010
DOI: 10.1080/10826068.2010.525432
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR STRUCTURAL STUDIES OF LICHEN SUBSTANCES WITH ANTIMICROBIAL, ANTIPROLIFERATIVE, AND CYTOTOXIC EFFECTS FROMParmelia subrudecta

Abstract: Lecanoric acid (1), orsellinic acid methyl ester (2), orcinol (3), and usnic acid (4) were isolated from the lichen Parmelia subrudecta, collected on Palma of the Canary Islands, Spain. Compounds 1, 2, 3, and 4 were purified by solvent extraction, silica gel column chromatography, and preparative high-performance liquid chromatography (HPLC) consecutively. The structures of the four compounds were elucidated by one- and two-dimensional nuclear magnetic resonance (NMR) experiments and mass spectrometric investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…2 Another study showed that only the Disomer is allergenic. 56,57 Another study revealed that both the D-and L-isomers of UA were allergenic and that persons may react to one or both enantiomers. 2 In 2006 study, it was reported that "four patients had positive patch test reactions to lichen acid mix and D-UA".…”
Section: Usnic Acid Induced Allergenicitymentioning
confidence: 99%
“…2 Another study showed that only the Disomer is allergenic. 56,57 Another study revealed that both the D-and L-isomers of UA were allergenic and that persons may react to one or both enantiomers. 2 In 2006 study, it was reported that "four patients had positive patch test reactions to lichen acid mix and D-UA".…”
Section: Usnic Acid Induced Allergenicitymentioning
confidence: 99%
“…This is the first time reporting from this plant and it had been previously isolated from lichen Parmelia subrudecta (Ivanova et al 2010). Compound III was identified as β -sitosterol as its spectral data matched with the reported data (El-Lakany et al 2004).…”
Section: Resultsmentioning
confidence: 77%
“…Also, in recent years (Bogo et al 2010), it has been shown that lecanoric acid, (para-depside) a secondary metabolite of the lichen Parmotrema tinctorum, has moderate antitumor activity against some malignant cell lines (MCF-7 breast carcinoma, 786-0 kidney carcinoma, and B16-F10 murine melanoma) tested. Similarly, some cytotoxic activity in vitro of lecanoric acid and orsellinic acid methyl ester, orcinol, and usnic acid isolated from the lichen Parmelia subrudecta is shown by other authors (Ivanova et al 2010). The depsides resulting from decarboxylation of baeomycesic and squamatic acids showed antiproliferative effects on PC-3 prostate cancer cells (Haraldsd ottir et al 2004;Brandão et al 2013).…”
Section: Depsides and Depsidonesmentioning
confidence: 67%